2015
DOI: 10.2217/pgs.14.177
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Association Studies and Meta-Analyses of MTHFR Gene Polymorphisms in Colorectal Cancer

Abstract: There is a discrepancy between the results of 89 original studies and 15 meta-analyses investigating the association of MTHFR rs1801133 and rs1801131 polymorphisms with colorectal cancer (CRC) risk. We examined this hypothesis through meta-analyses of both loci and their diplotypes as well as evaluation of previous meta-analyses. The present meta-analysis showed that rs1801133 and rs1801131 might be CRC susceptibility variants in Americans and Australians and rs1801133 in Brazilians and Japanese. A strong link… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Consistent with the reports from previous meta-analyses, in the present pooled analyses for all populations, MTHFR 677 homozygous mutation TT genotype presented as a protective genotype for CRC with statistical significance ( p < .05); however, there were heterogeneity and opposing findings for the subgroup of Hispanics ( p < .01). Previous meta-analyses consistently indicated heterogeneity or discrepancies for MTHFR and CRC risk for various populations, perhaps due in part to the dominant population stratification from Australia, the United States, and Brazil ( Haerian & Haerian, 2015 ). In this meta-analysis study, the subgroup analysis with those countries that had findings contrary to those majority countries with the MTHFR 677 TT homozygous mutation genotype as a protective type was revealing to delineate the impacts of population stratification.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with the reports from previous meta-analyses, in the present pooled analyses for all populations, MTHFR 677 homozygous mutation TT genotype presented as a protective genotype for CRC with statistical significance ( p < .05); however, there were heterogeneity and opposing findings for the subgroup of Hispanics ( p < .01). Previous meta-analyses consistently indicated heterogeneity or discrepancies for MTHFR and CRC risk for various populations, perhaps due in part to the dominant population stratification from Australia, the United States, and Brazil ( Haerian & Haerian, 2015 ). In this meta-analysis study, the subgroup analysis with those countries that had findings contrary to those majority countries with the MTHFR 677 TT homozygous mutation genotype as a protective type was revealing to delineate the impacts of population stratification.…”
Section: Discussionmentioning
confidence: 99%
“…Linkage disequilibrium among the variants can vary across populations . For example, Haerian and Haerian showed that rs1801133 and rs1801131 might be CRC susceptibility variants in Americans and Australians, whereas rs1801133 may be more common in the Brazilian and Japanese populations. Based on these results, patients of different ethnicities may carry different rs1801133 and rs1801131 variants.…”
Section: Methodsmentioning
confidence: 99%
“…In recent years, there were several meta-analyses performed to elucidate the association of MTHFR C677T polymorphism and the susceptibility to CRC before [ 26 , 115 118 ]. Compared with them, this meta-analysis included the most eligible reported studies with the largest sample size and had no restrictions in ethnicity.…”
Section: Discussionmentioning
confidence: 99%